Factors Influencing Career Choice among Undergraduate Students of Pokhara University in Kathmandu - Joshi, Ranju; Rawat, Ramesh (Nepalese Journal of Economics, 2025)
This study examines the factors influencing career choice among undergraduate students of Pokhara University in Kathmandu. Career choice is the dependent variable. The selected independent variables are family influence, future job opportunities, personal interest, financial outcomes, and peer influence. The primary source of data is used to assess the opinions of respondents regarding family influence, future job opportunities, personal interest, financial outcomes, peer influence, and career choice. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of career choice among undergraduate students of Pokhara University in Kathmandu. The study showed a positive impact of family influence on career choice. It indicates that family support leads to better career choice decision. Similarly, the study showed a positive impact of future job opportunities on career choice. It indicates that better future job opportunities attract students to pursue career in interested field. Likewise, the study also revealed a positive impact of personal interest on career choice. It indicates that students who are personally interested in a particular field are more likely to excel in it. Further, the study observed a positive impact of financial outcomes on career choice. It indicates that higher the financial outcomes leads to influence the career choice decision of the students. In addition, the study observed a positive impact of peer influence on career choice. It indicates that peer influence leads to encourage while choosing career.